Interpreting Primo Levi
XI, 281 p.
Keywords: This collection contains new and innovative research into the work of the Italian antifascist partisan, concentration camp survivor, author and thinker Primo Levi (1919–1987). It features original essays by many of the world's foremost Levi scholars and by specialists in fields as varied as education, theology, and fine art. Levi's legacy continues to drive a vibrant, continually evolving body of interdisciplinary scholarship, as the contributions to this intellectually rich, tightly organized volume confirm. The essays gathered here demonstrate a remarkable breadth across five distinct yet interrelated areas: ethics, communication, and education; humanity, animality, and science; the camps: memory and space; literature and intertext; and media, publishing, and illustration.